Intercultural Learning in the Experience of Polish Teachers after the Outbreak of the War in Ukraine, 2022 - Popow, Monika (INSTED: Interdisciplinary Studies in Education & Society, 2024)
The article addresses the issue of teachers intercultural learning after the outbreak of war in Ukraine in 2022. For the analysis, I use three categories – intercultural learning, intercultural competence and a critical incident – which are introduced simultaneously because of the particular socio-political context in which the teachers found themselves. The analysis shows that intercultural learning occurs primarily at the level of building knowledge about the Other and building engagement. However, teachers do not transfer the experience to the general level or do not professionalize it.